2,2′-Azobis (2-Amidinopropane) Dihydrochloride Is a Useful Tool to Impair Lung Function in Rats - Moreira Gomes, Maria D.; Carvalho, Giovanna M. C.; Casquilho, Natalia V.; Araújo, Andressa C. P.; Valença, Samuel S.; Leal-Cardoso, Jose H.; Zin, Walter A. (Frontiers in Physiology, 2016)
Recently, several studies have reported that respiratory disease may be associated with an increased production of free radicals. In this context, 2,2′-azobis (2-amidinopropane) dihydrochloride (AAPH) is a free radical-generating compound widely used to mimic the oxidative stress state. We aimed to investigate whether AAPH can generate lung functional, inflammatory, histological and biochemical impairments in the lung. Wistar rats were divided into five groups and instilled with saline solution (714 μL/kg, CTRL group) or different amounts of AAPH (25, 50, 100, and 200 mg/kg, 714 μL/kg, AAPH groups). Seventy-two hours later the animals were anesthetized, paralyzed, intubated and static elastance (Est), viscoelastic component of elastance (ΔE), resistive (ΔP1) and viscoelastic (ΔP2) pressures were measured. Oxidative damage, inflammatory markers and lung morphometry were analyzed. ΔP1 and Est were significantly higher in AAPH100 and AAPH200 than in the other groups. The bronchoconstriction indexes were larger in AAPH groups than in CTRL. The area occupied by collagen and elastic fibers, polymorpho- and mononuclear cells, malondialdehyde and carbonyl groups levels were significantly higher in AAPH200 than in CTRL. In comparison to CTRL, AAPH200 showed significant decrease and increase in the activities of superoxide dismutase and catalase, respectively. AAPH augmented the release of pro-inflammatory cytokines IL-1β, IL-6 e TNF-α. Hence, exposure to AAPH caused significant inflammatory alterations and redox imbalance accompanied by altered lung mechanics and histology. Furthermore, we disclosed that exposure to AAPH may represent a useful in vivo tool to trigger lung lesions.